ENVIRONMENTAL-ECONOMIC ACCOUNTING AND ASSESS THE EFFECTIVENESS OF ENVIRONMENTAL MANAGEMENT - Anatoly Belousov; Lilia Blizno (Вестник Северо-Кавказского федерального университета, 2022)
The article discusses the reflection of natural assets in national accounts meso- and megaeconomic level. The peculiarities of valuation of natural assets as a complex ecological-economic categories, which should be oriented not on the market, and the fair value. As the main directions of development of environmental-economic accounting of natural assets should be recognized as full-fledged creation, and, most importantly, the real functioning of the integrated reporting framework based on sustainable development principles.